2008
DOI: 10.2308/acch.2008.22.4.375
|View full text |Cite
|
Sign up to set email alerts
|

The Need for an Internal Auditor Report to External Stakeholders to Improve Governance Transparency

Abstract: SYNOPSIS: This paper considers the need for an internal audit report ͑IAR͒ to increase governance transparency for external stakeholders. While the internal audit function is an important and distinct governance mechanism, external stakeholders typically lack the direct relevant information about the function that is available to insiders from other governance mechanisms ͑e.g., management, audit committee, and external auditor͒. This information asymmetry is inconsistent with current objectives for governance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 27 publications
2
51
0
3
Order By: Relevance
“…suggest that IAF quality is a good predictor of accounting-related management misconduct and provide empirical evidence of the claims of stakeholders in Archambeault et al (2008) that disclosure of IAF quality could be beneficial to the market.…”
Section: Predicting Accounting-related Management Misconductmentioning
confidence: 91%
“…suggest that IAF quality is a good predictor of accounting-related management misconduct and provide empirical evidence of the claims of stakeholders in Archambeault et al (2008) that disclosure of IAF quality could be beneficial to the market.…”
Section: Predicting Accounting-related Management Misconductmentioning
confidence: 91%
“…Les relations entre l'audit interne et le comité d'audit L'audit interne est l'un des pivots de la gouvernance des organisations (Archambeault, DeZoort et Holt, 2008 ;Gramling et autres, 2004 ;Holt et DeZoort, 2009 ;Mat Zain et Subramaniam, 2007 ;Prawitt, Smith et Wood, 2009 ;Rezaee, 2005). Ce point de vue est partagé par les directeurs de la fonction d'audit interne qui se considèrent comme faisant partie intégrante de la gouvernance (Buranby et Hass, 2009, p. 822).…”
Section: Les Relations Entre L'audit Interne Et Le Comité D'audit Et unclassified
“…External stakeholders such as investors generally lack information related to the IAF. Survey and experimental research report that disclosure of information related to the IAF would increase stakeholder confidence in governance quality and potentially affect investment decisions (Archambeault et al 2008;Holt and DeZoort 2009). I find that IAF quality is negatively associated with accounting-related management misconduct even after controlling for observable predictors of accountingrelated management misconduct (see Dechow et al 2011).…”
Section: Using Proprietary Internal Audit Survey Data From the Institmentioning
confidence: 86%
“…This provides insight into whether disclosures of IAF quality would be informative to investors. Interviewees in Archambeault et al (2008) state that a report on internal audit would not only be useful to various stakeholders, but could also increase IAF accountability and incentives to perform effectively. Holt and DeZoort (2009) found that participants in their experiment were more confident in financial reporting reliability and perceived the oversight of financial reporting to be more effective when provided with an internal audit report.…”
Section: Predicting Accounting-related Management Misconductmentioning
confidence: 99%